Russian Orthodox Church, Port Moller, ca. 1912 - Thwaites, John E. (John Edward), 1863-1940 (1912)
Caption on image: Native Chapel, Russian, Port Moller, Alaska PH Coll 247.909 Port Moller is a village in southwest Alaska. It is located on the Alaska Peninsula at the entrance of Port Moller Inlet (20 mi long) of Bristol Bay on the Bering Sea. Primary industries are fishing and fish canning.